A Holistic Reader in Applied Anthropology: The Target of Health in Ethiopia, - Messing, Simon D. (MSS Information Corp, 1973)
Keywords: Ethiopia; Medical anthropology; Applied anthropology; Ethnology; dept.ant; faculty_collection

Encyclopedia of Anthropology - Hunter, David E.; Whitten, Phillip (Harper & Row, 1976)
Keywords: Anthropology; Dictionaries; dept.ant; faculty_collection

The study of anthropology - Hunter, David E.; Whitten, Phillip (Harper & Row, 1976)
Keywords: Anthropology; dept.ant; faculty_collection

Ethiopian revolution [3] - Messing, S.D. (Science, 1975)
Keywords: dept.ant

Social problems related to the development of health in Ethiopia - Messing, S.D. (Social Science and Medicine, 1970)
The relationship between the development of public health programs and "social problems" is of increasing concern to students of social and cultural problems. Health is obviously related to the availability of good nutrition, essential in building resistance against contagious diseases that form the bulk of preventable health problems in underdeveloped countries. Good nutrition, in turn, is dependent upon availability of agricultural products, basic income to buy them, and education to utilize them properly. This article attempts to trace, briefly, some of the etiology of these interrelated problems in a country in which traditional values have not been distorted by a foreign-established colonial period, and which has experienced only superficial change in modern times. This makes it possible to view relationships more clearly than in other underdeveloped countries where they may exist in more complex forms. © 1970.
Keywords: Agriculture; Attitude to Health; Circumcision; Ethiopia; Folklore; Government; Health Planning; Human; Nutrition; Public Health; Rural Health; Social Change; Socioeconomic Factors; Taboo; Urbanization; agriculture; article; attitude; circumcision; cultural anthropology; dept.ant; ethnic group; government; health; health care planning; human; nutrition; public health; socioeconomics; sociology; urbanization

Two tactics for ethnic survival-Eskimo ℰ Indian - Dryfoos, Robert J. (Trans-action, 1970)
Keywords: dept.ant

State of Blood, the Inside Story of Amin,idi - Kyemba,h - Messing, SD (Africa Today, 1979)
Keywords: dept.ant; ⛔ No DOI found

The quest for therapy in lower zaire. john m. janzen, with the collaboration of william arkinstall. - Messing, Simon D (Medical Anthropology Newsletter, 1979)
Keywords: dept.ant

On becoming gleichgeschaltet - Messing, Srmon D; Clmino, Louis (Anthropology News, 1979)
Keywords: dept.ant

Racism in the census - Messing, Simon D (Anthropology News, 1978)
Keywords: dept.ant

Anthropology and Nazi Genocide - Messing, SD (Current Anthropology, 1976)
Keywords: dept.ant

Book Review: Greater ethiopia: the evolution of a multiethnic society . Levine Donald n. . Chicago: University of Chicago Press, 1974. 229 pp. 12.50 - Messing, Simon D (ASA Review of Books, 1976)
Keywords: book.review; dept.ant; ⚠️ Invalid DOI

Affirmative-Action and Image of Limited Good - Messing, SD (Current Anthropology, 1975)
Keywords: dept.ant; ⛔ No DOI found

Health-Care, Ethnic Outcasting, and Problem of Overcoming Syndrome of Encapsulation in a Peasant Society - Messing, SD (Human Organization, 1975)
Keywords: dept.ant

Discounting health: The issue of subsistence and care in an undeveloped country - Messing, Simon D (Social Science & Medicine, 1973)
The concept "discounting health" is proposed as a heuristic model for analysis of differing perceptions concerning "cost-benefit", as these relate to systems of health care. This procedure became necessary during analysis of data gathered in rural Ethiopia to measure the effectiveness of new Health Centers. Ethnological research accompanying the quantitative study of health attitudes found that "subsistence anxiety" dominated all other concerns of the majority in the rural areas. The landless peasant sharecropper and his divorced wife represent the most prevalent social problem in Ethiopia. Holistic solutions should include some form of social security and safe wells, so that the population can stop "discounting health". © 1973.
Keywords: Absenteeism; Anxiety; Attitude to Health; Child; Community Health Services; Delivery of Health Care; Economics; Epidemiology; Ethiopia; Ethnic Groups; Health Education; Human; Income; Legislation, Medical; Life Style; Models, Theoretical; Preventive Health Services; Questionnaires; Rural Health; Sanitation; anxiety; dept.ant; developing country; finance; health center; health service; methodology; model; primary health care; public health service

Book Review: Customary law and modernization - afrika-spectrum: law in east africa . hamburg: deutsches institut für Afrika-Forschung, 1970 (no. 3, 1969). 80 pp. - Messing, Simon D (African Studies Review, 1971)
Keywords: book.review; dept.ant